Levels of motivation types among men's volleyball teams in a prestigious collegiate league a comparative analysis between top two and bottom teams - Nasol, John Miguel B. 1995-; Maghanoy, Mona Liza A. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2019)
Motivation is a widely-researched factor when it comes to performance, which can be related to the field of sport. The focus is on determining the level of motivation types among UAAP Men's Volleyball varsity student-athletes. Along with this, the proponent of this study aimed to know if there were differences in the levels of motivation types among the top-performing teams from those that are from the bottom teams. There were a total of 54 participants from the top two and bottom two UAAP Men's Volleyball teams, based on the rankings from the recently concluded UAAP Season 81. Using the Sport Motivation Scale Pelletier et.al. (1995), the levels of motivation types among these teams were examined. Descriptive Statistics and Independent Sample T-test were used through the use of SPSS to analyze the data. Descriptive Statistics show that the top two teams scored highest in Identified Regulation. Meanwhile, both groups scored high on all types of Intrinsic Motivation. On the other hand, Independent Sample T-test revealed that there was a significant difference in Identified Regulation and External Regulation between the top two teams and the bottom two teams.
Vita.
Thesis (Bachelor in Sports Science)--University of the Philippines Diliman
Keywords: Motivation (Psychology).; Sports -- Psychological aspects; College athletes -- Philippines